(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Recent excavations in the quarter of Las Burgas, in the province of Orense, have brought to light the remains of the Roman ritual spa, including a number of votive aras with the godname REVE ANABARAECO on them. Several tentative etymologies of the divine epithet are offered.